Alteration of Metformin Pharmacokinetic Profile in Rats Exposed to a Low Dose of Chlorpyrifos Insecticide - Desie Dwi Wisudanti; Cholis Abrori; Cicih Komariah; Supangat Supangat; Elly Nurus Sakinah (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Chlorpyrifos (CPF) is an organophosphate pesticide widely used by farmers to control pests and has a broad spectrum of action. Research has shown that organophosphate pesticides can affect efflux pumps, specifically P-glycoprotein (P-gp), which can alter drug absorption and metabolism, indicating the potential risk of changes in a drug's pharmacokinetic profile, which could affect the effectiveness of drugs such as Metformin. This study investigated the impact of low-dose CPF exposure on the pharmacokinetic profile of Metformin, a first-line treatment for type 2 diabetes mellitus (T2DM). This study used 16 rats to examine Metformin's pharmacokinetic profile and 12 for the creatinine clearance examination. The rats were divided into two groups: a control group given normal saline (+5% Tween 20) and a group given CPF 5 mg/kg BW/day, each administered for 7 days. Metformin was administered on day 8, and pharmacokinetic parameters were assessed using UV-HPLC by measuring metformin plasma levels at 0.5, 1, 2, 4, 6, 8, 12, and 24 hours. Serum creatinine levels were examined in 12 rats using the Jaffe method on day 8 after treatment. The pharmacokinetic analysis showed that there was a change in the metformin profile following CPF administration: an increase in the area under the curve (AUC) and peak concentration (Cmax), along with a decrease in time to peak concentration (Tmax), half-life (T½), clearance (Cl), and volume of distribution (Vd). Serum creatinine levels in the CPF-administered group increased significantly (p<0.05). Further research, including pharmacodynamic assessment and clinical trials, is recommended to guide therapeutic decisions in populations with pesticide exposure.